Managing stress : principles and strategies for health and wellbeing - Seaward, Brian Luke (Sudbury, Mass. : Jones and Bartlett Publishers, 2006)
Accompanying CD-ROM contains free relaxation audio selections
The nature of stress -- The physiology of stress -- Stress and disease -- The mind and soul -- Toward a psychology of stress -- The stress emotions: anger and fear -- Stress-prone and stress-resistant personalities -- Stress and human spirituality -- Coping strategies -- Cognitive restructuring -- Behavior modification -- Journal writing -- Expressive art therapy -- Humor therapy (comic relief) -- Creative problem solving/reframing -- Communication skills -- Resource management: managing time and money -- Additional coping techniques -- Relaxation techniques -- Diaphragmatic breathing -- Meditation -- Hatha yoga -- Mental imagery and visualization -- Music therapy -- Massage therapy -- T'ai chi ch'uan -- Progressive muscular relaxation -- Autogenic training -- Clinical biofeedback -- Nutrition and stress -- Physical exercise
Includes bibliographical references and index
Accompanying CD-ROM system requirements: Windows; Audio speakers and capability
Keywords: Mind and body; Stress (Psychology); Stress management